MINAT MAHASISWA AKUNTANSI MERAIH GELAR PROFESI CHARTERED ACCOUNTANT (CA) - Simorangkir, Panubut (EQUITY: Jurnal Ekonomi, Manajemen, Akuntansi, 2018)
The purpose of this study was to obtain an overview of the knowledge and interests of students following the PPAk. This research was conducted by distributing research instruments in the form of questionnaires that were given directly to students who would complete their studies in the S 1 Accounting study program. Students who willbe asked to become respondents are asked to fill out a questionnaire. Grade Point Average (GPA) of students who are respondents above 3.25. The results showed that the existence of PPAk was not fully understood so that there were differences in motivation among respondents. Relevant students are very strongly influenced by the desire to get a job / career, whereas for extension students who generally have worked the interest in obtaining a CA degree is motivated by other than a desire for a career but also a desire to improve the quality of professionalism in accounting. Thus, it seems that the extension of students' understanding of the existence of PPAk is more comprehensive compared to regular students.